Analysis, synthesis, and design of chemical processes (Prentice Hall PTR, 1998)
Analysis, Synthesis, and Design of Chemical Processes presents a holistic approach to process design, walking through each step from initial process cost estimation to final process optimization. "The emphasis on solving open-ended problems gives students a taste of real-life engineering in place of artificial classroom exercises. By stressing macro-level analysis, Analysis, Synthesis, and Design of Chemical